92.5k views
2 votes
If f(x) = x2 and g(x) = 3x - 1 find [ gºf(x)​

User Tao Nhu
by
4.5k points

1 Answer

1 vote

Answer:

gºf(x)​ =
3x^2 -1

Explanation:

Given

f(x) = x2

g(x) = 3x - 1

To find

gºf(x)​

To find gºf(x)​ we will use value of f(x) =
x^2 in place of in g(x)

lets do that

g(x) = 3x - 1

gºf(x)​ = 3(f(x)) -1

gºf(x)​ =
3x^2 -1

Thus, value of gºf(x)​ is
3x^2 -1.

User EyecatchUp
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.